Interaction between proteins and Ir based CO releasing molecules: Mechanism of adduct formation and CO release - Petruk, Ariel Alcides (2014)
Carbon monoxide releasing molecules (CORMs) have important bactericidal, anti-inflammatory, neuroprotective, and antiapoptotic effects and can be used as tools for CO physiology experiments, including studies on vasodilation. In this context, a new class of CO releasing molecules, based on pentachlorocarbonyliridate(III) derivative have been recently reported. Although there is a growing interest in the characterization of protein–CORMs interactions, only limited structural information on CORM binding to protein and CO release has been available to date. Here, we report six different crystal structures describing events ranging from CORM entrance into the protein crystal up to the CO release and a biophysical characterization by isothermal titration calorimetry, Raman microspectroscopy, and molecular dynamics simulations of the complex between a pentachlorocarbonyliridate(III) derivative and hen egg white lysozyme, a model protein. Altogether, the data indicate the formation of a complex in which the ligand can bind to different sites of the protein surface and provide clues on the mechanism of adduct formation and CO release.